(untitled) (Bulletin of Kharkiv National University of Internal Affairs, 2023)
The article demonstrates the doctrinal interpretations of digitalisation as a general legal phenomenon. The emphasis is placed on the fact that the analysis of the content of scientific publications in the field of digitalisation of social relations indicates that priority in this area is still given to highly specialised issues which are studied mainly within the framework of branch legal sciences, primarily constitutional, judicial, administrative and civil law. Therefore, the study of digitalisation usually lacks a comprehensive nature, since the relevant issues are analysed without clarifying the conceptual basis of digitalisation. The approaches proposed in the national legal science to improve certain legal regulators and reorient legislation to regulate social relations in the field of digitalisation often fall behind the rapid development of the relevant processes. It is indicated that along with traditional law which is rapidly being digitised (moving into the virtual space from paper carriers), the phenomenon of digital law is emerging which is an intersectoral formation mediating social relations which take place in the virtual space (from cryptocurrency circulation to the provision of administrative services). Furthermore, emphasis is placed on the fact that in practice, the formation of new legal models of digitalisation of public relations in general and public administration in particular takes place outside the doctrine of social relations legalisation which has been developed by theoretical and legal science. Such an approach fundamentally contradicts the existing social needs, leads to managerial and law-making chaos and the lack of distinction between the truly objective needs for legal regulation of new relations and opportunistic managerial decisions which only selectively stimulate the regulatory impact of law on digitalisation. It also fails to ensure timely and effective legal regulation of the relevant range of rapidly emerging social relations that significantly transform the conventional way of life of society, the political, legal and value “image” of the state, its institutional and functional foundations, as well as the lifestyle of each citizen, including the set of his or her personal rights exercised in the public life of the digital age.